Secured by design establishing design guidelines against crime in urban communities of Tacloban City - Borja, Bryan Steven E. (2023)
The Defensible Space theory was developed by architect and planner Oscar Newman with the idea that the physical environment influences criminal behavior. In spite of its initial success, several scholars found inconsistencies in Newman?s theory and as well as highlighted its lack of association of social factors. These scholars argued that although the theory captures the possible aspects of the built environment that can influence criminal behavior, it lacks the mechanism to fully encapsulate the concept of crime prevention through environmental design. This paper attempts to integrate Newman?s Defensible Space theory with the theory of Sense of Community, in hopes of amending this gap in the framework and strengthening the current body of literature of crime prevention through design.Through mapping, thematic, and correlational analysis, this thesis generated crime mitigative and preventive guidelines on how to design safe communities, and it was also found out that our physically deterministic views on crime is brought upon by our primitive habits of assessing our physical environment of cues for safety, and that a certain time threshold must be passed for a community to transition from perceiving and being dependent on safety as a physically deterministic phenomena to a passive socially-influenced one.